TANTANGAN DAN STRATEGI PERKEMBANGAN PERBANKAN SYARIAH DI INDONESIA - Muhammad Iqbal Fasa (University of Darussalam Gontor, 2013)
This research tries to offer a solution to face the challenges of Islamic banks nowadays. It is known that Islamic banking in Indonesia was reached twentieth age, but has only 5 % from total market share in Indonesia. This is a contradiction to the fact that Indonesia is a largest muslim country in the world. This problem is related to some factors. First, muslim’s rationality in economic, which doesn’t consider halal or haram to pursue the material wealth. Second, their lack of understanding of Islamic bank. Third, there is no support from Islamic institution. Fourth, Islamic banks in Indonesia operate in mix economic system which has lack of regulation, because system of control is mixed with the conventional banks. Therefore, it is necessary to formulate the strategy of Islamic banks development to face the competition with the conventional. It is directed to the development of business competency comprehensively referring to the strength and weaknesses analysis of Islamic banks in Indonesia, such as new imaging program, expansion of market share program, development product program, service enhancement program and open and universal communication program.